Synthesis of phosphorus(V)-stabilized geminal dianions : the cases of mixed P═X/P→BH3 (X = S, O) and P═S/SiMe3 derivatives - Heuclin, Hadrien (2013)
The monodeprotonation of [CH2(PPh2→BH3)(PPh2═E)] (E = S (6), O (7)) afforded [CH(PPh2→BH3)(PPh2═E)]− (E = S (6-), O (7–)), whose structures were confirmed by X-ray crystallography. The kinetics of the second deprotonation appeared to be crucial in efficient synthesis of the corresponding dianions. Thus, the double deprotonation of 6 only led to 62–; the analogous reaction with 7 was slower and resulted only in the partial formation of 72–. Double deprotonation of the compound [CH2(SiMe3)(PPh2═S)] (8) also resulted in the partial formation of [C(SiMe3)(PPh2═S)]2- (82–), whose structure was confirmed by X-ray crystallography. The rare monomeric Mg carbene compound [MgC(PPh2→BH3)(PPh2═S)] (9) was obtained by the reaction of 6 with Mg(nBu)2. The X-ray structure of 9 is presented.